Agapetes hongheensis (Ericaceae), a new species from Yunnan, China - Chun-Yu Zou; Bing-Mou Wang; Yu-Song Huang; Yi-Hua Tong (PhytoKeys)
Agapetes hongheensis, a new species of Ericaceae from Yunnan, China, is described and illustrated. This new species resembles A. mannii and A. hosseana, but differs from the former by its linear or narrowly oblong and bullate leaf blade with a strongly recurved leaf margin and obvious reticulate veinlets adaxially, and larger flowers with yellow green and glabrous corollas and longer stamens, and can be distinguished from the latter by having glabrous twigs, linear or narrowly oblong leaf blades, yellow green corollas and exerted style.